The Effect of Inflation on Inflation Uncertainty in the G7 Countries: A Double Threshold GARCH Model - Kushal Banik Chowdhury; Nityananda Sarkar (International Econometric Review (IER), 2015)
This paper studies the impact of inflation on inflation uncertainty in a modelling framework where both the conditional mean and conditional variance of inflation are regime specific, and the GARCH model for inflation uncertainty is extended by including a lagged inflation term in each regime. Applying this model to the G7 countries with monthly data from 1970 till 2013, it is found that the impact of inflation on inflation uncertainty differs over the regimes in most of the G7 countries. The findings also provide strong empirical support to the well-known Friedman-Ball hypothesis of positive impact of inflation on inflation uncertainty, but only for the high-inflation regime.
Keywords: C22; E31; 330; Inflation; Inflation Uncertainty; Regime Switching Model